(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article provides a detailed comparative analysis of mood verbs in the Uzbek and English languages. It examines the similarities and differences in how mood is expressed through verbs in both languages, considering aspects such as verb categories, conjugation, cultural influence, pragmatic considerations, and linguistic borrowing. Through this analysis, the article offers insights into the linguistic structures and cultural nuances of Uzbek and English, shedding light on the diverse ways in which mood is conveyed in these languages